Comparison of Postoperative Sensitivity in Class I Amalgam Restorations using Copal Varnish Versus Dentin Bonding Agent: A Randomized Control Trial - Samreen Aqeel, Saood Khan Lodhi, Saroosh Ehsan, Adeela Rafique, Khalid Saeed Mirza, Haris Naeem Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy of Copal varnish versus dentin bonding agent for the prevention of postoperative sensitivity in amalgam restorations with the help of Visual auditory score (VAS). Study Design: Comparative clinical study. Place and Duration: A randomized control trial was conducted in the Department of Operative Dentistry after approval from the Institutional Review Board (IRB) of Fatima Memorial Hospital (FMH-03-2020-IRB-752-M). Methodology: A randomized control trial was conducted in which sample size of 60 was calculated, 30 in group. A (copal varnish) and 30 in group B (dentin bonding agent) with 95% confidence level and 80% power of test, 5 % level of significance. Non-probability consecutive sampling was used using lottery method. Inclusion criteria included both male and female patients with age range 18-40 years and no significant signs and symptoms of pain prior to treatment. Teeth which were previously restored and deep cavities with less than 2mm of remaining dentin thickness on periapical radiograph, with reference to GV Black’s class I were excluded from the study. Results: The study subjects were 60 patients requiring restorations for class I cavities. Each treatment group had 30 patients. A single operator evaluated all the patients at baseline and performed the procedure. The patients were recalled at 24 hours and 7th day, for postoperative evaluation. No significant difference was found in the mean sensitivity score of both the classes. Chisquare test was analyzed to find out the frequency of postoperative sensitivity and efficacy among males and females. No significant difference was found among both males and females. Practical implication: Current study can help dentists choose the right materials for restorative procedures, reducing postoperative discomfort. It also highlights the importance of regular dental check-ups and early intervention to prevent invasive procedures and promote oral health for the community. Conclusion: Copal varnish and dentin bonding agents are equally good in terms of their efficacy and reduction of postoperative sensitivity, in class I amalgam restorations. The effect of cavity depth and amount of tooth reduction greatly affect the result of postoperative sensitivity in class I lesions confined to outer 1/3rd of dentin. Keywords: Copal varnish, dentin bonding agents, Amalgam, dentinal tubules